Pengaruh Penggunaan Cacing Tanah dan Kotoran Sapi pada Proses Pengomposan Limbah Organik Pasar terhadap Kualitas Kompos - Rizki Beril Yudatama; Bambang Hermiyanto (Jember University Press, 2023)
Garbage is material that is not used or remains from activities carried out by humans, generally in the form of solids, and this is also called waste. One of the most waste-producing environments is the market, especially the traditional market. This market waste is dominated by the type of organic waste. The solution to reducing market waste can be done by managing organic waste into compost. The composting process is closely related to decomposers, examples of decomposers are earthworms, bacteria, and fungi. This study aims to determine the effect of the interaction between the treatment of earthworms and cow manure on compost quality. The study used a factorial completely randomized design (CRD) with 2 factors and was repeated 3 times. The first factor was the number of earthworms consisting of no earthworms (C0), using 60 earthworms (C1), and using 120 earthworms (C2). The second factor was the amount of cow manure which consisted of no cow manure (K0), with 22.5% cow manure (K1) and 45% cow manure (K2). The variables observed included the quality of the compost by looking at the color, smell, texture, temperature, C-organic, N-total, P2O5, K2O, and C/N ratio. Data were analyzed by Analysis of Variety. If it is significantly different, it will be tested further with Duncan's 5% Multiple Range Test. The combination of C0K0 treatment had the highest C-organic, N-total, P2O5, and K2O values. The C0K1 combination has the highest C/N ratio..